Thermally conductive sheet and manufacturing method thereof
The thermally conductive sheet with a scaly filler oriented in a specific manner within a polymer matrix addresses the inefficiencies of conventional sheets by enhancing thermal conductivity in both the thickness and surface directions, improving heat dissipation and managing heat transfer effectively.
Patent Information
- Application Number
- JP2024220885
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-01
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-10-26
AI Technical Summary
Conventional thermally conductive sheets have inferior thermal conductivity in the thickness direction, making them less efficient in transmitting heat from heating elements to heat radiators, and they struggle to suppress heat conduction in specific directions.
A thermally conductive sheet with a scaly filler oriented in a specific manner within a polymer matrix, where the longitudinal direction of the scale surface is aligned either with the thickness direction or perpendicular to it, and the horizontal axis direction is aligned in the other direction, enhancing thermal conductivity in both the thickness and surface directions.
The sheet achieves high thermal conductivity not only in the thickness direction but also in one direction along the surface direction, improving heat dissipation and preventing heat spots, while maintaining low thermal conductivity in other directions to manage heat transfer effectively.
Smart Images

Figure 2025038119000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet and a method for producing the same. [Background technology]
[0002] In electronic devices such as computers, automobile parts, and mobile phones, heat sinks and other heat dissipators are commonly used to dissipate heat generated from heat generating bodies such as semiconductor elements and machine parts. It is known that a thermally conductive sheet is disposed between the heat generating body and the heat dissipator in order to increase the efficiency of heat transfer to the heat dissipator. A thermally conductive sheet generally contains a polymer matrix and a thermally conductive filler dispersed in the polymer matrix. In addition, the thermally conductive sheet may have an anisotropic filler having an anisotropic shape oriented in one direction in order to enhance thermal conductivity in a specific direction.
[0003] A thermally conductive sheet in which anisotropic filler is oriented in one direction is manufactured, for example, by preparing a plurality of primary sheets in which anisotropic filler such as fibrous filler is oriented along the sheet surface direction by stretching or the like, and vertically slicing the resulting laminated and integrated primary sheets. According to this manufacturing method (hereinafter also referred to as the "flow orientation method"), a thermally conductive sheet is obtained which is composed of a large number of unit layers of minute thicknesses laminated together. In addition, the anisotropic filler can be oriented in the thickness direction of the sheet, and the thermal conductivity in the thickness direction is improved (for example, see Patent Document 1). The thermally conductive sheet has high thermal conductivity in the thickness direction, and therefore it is possible to efficiently dissipate heat generated by a heat generating body inside an electronic device to the outside. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-27144 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, heat spots may occur inside electronic devices, where the temperature rises locally. To eliminate heat spots, a heat diffusion sheet with excellent thermal conductivity in the plane direction may be used. In addition, since the heat resistance of electronic elements generally differs depending on the type of electronic element, for example, when an element with low heat resistance exists on a substrate, it is necessary to prevent heat transfer in that direction. In that case, it is required to increase the thermal conductivity in a specific direction in the plane while decreasing the thermal conductivity in a direction other than that direction. However, conventional heat diffusion sheets have poor thermal conductivity in the thickness direction, so they are poor in the efficiency of transferring heat generated by the heating element to the heat sink, and also diffuse heat isotropically, making it difficult to suppress heat transfer in a specific direction. On the other hand, thermally conductive sheets in which anisotropic filler is oriented in the thickness direction of the sheet, as obtained by conventional flow orientation methods, are highly efficient at transferring heat generated by the heating element to the heat sink, but it is difficult to increase the thermal conductivity in the direction along the surface of the sheet.
[0006] Therefore, an object of the present invention is to provide a thermally conductive sheet that has high thermal conductivity not only in the thickness direction of the sheet, but also in one direction along the surface direction of the sheet. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by the following configurations, and have completed the present invention. That is, the present invention provides the following [1] to
[12] . [1] A thermally conductive sheet containing a scale-like filler in a polymer matrix, A thermally conductive sheet in which the long axis direction of the scale-like filler surface is oriented along either a first direction, which is the thickness direction of the thermally conductive sheet, or a second direction perpendicular to the first direction, and the horizontal axis direction perpendicular to the long axis direction on the scale surface is oriented along the other of the first direction and the second direction. [2] The thermally conductive sheet described in [1] above, wherein the scale-like filler is oriented such that the major axis direction is along the first direction and the horizontal axis direction is along the second direction. [3] The thermally conductive sheet described in [1] above, wherein the scale-like filler is oriented such that the horizontal axis direction is along the first direction and the long axis direction is along the second direction. [4] A thermally conductive sheet according to any one of the above [1] to [3], wherein the first aspect ratio, expressed as the ratio of the length in the long axis direction to the length in the horizontal axis direction of the scaly filler (length in the long axis direction / length in the horizontal axis direction), is 1.5 or more. [5] The thermally conductive sheet according to any one of the above [1] to [4], wherein the average particle size of the scaly filler is 20 μm or more. [6] The thermally conductive sheet according to any one of the above [1] to [5], wherein the scaly filler contains scaly graphite powder. [7] The thermally conductive sheet according to any one of the above [1] to [6], wherein the scaly filler contains scaly boron nitride powder. [8] The thermally conductive sheet according to any one of the above [1] to [7], further comprising a fibrous filler in the polymer matrix. [9] The thermally conductive sheet according to the above [8], wherein the fibrous filler is carbon fiber.
[10] A laminate having a plurality of unit layers, at least one of the plurality of unit layers including the scaly filler; The thermally conductive sheet according to any one of the above [1] to [9], wherein a plurality of unit layers are laminated along a third direction perpendicular to the first and second directions.
[11] The thermally conductive sheet according to any one of the above [1] to
[10] , further comprising a non-anisotropic filler in the polymer matrix.
[12] A method for producing a thermally conductive sheet according to any one of the above [1] to
[11] , A step of preparing a mixture containing a resin that is a precursor of the polymer matrix and the scaly filler; a step of subjecting the mixture to a flow orientation treatment to obtain a primary sheet while orienting the scaly filler; laminating the primary sheets to obtain a laminated block; cutting the laminated block along a lamination direction; A method for manufacturing a thermally conductive sheet comprising the steps of: Effect of the Invention
[0008] According to the present invention, it is possible to provide a thermally conductive sheet having high thermal conductivity not only in the thickness direction of the sheet, but also in one direction along the surface direction of the sheet. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic perspective view showing a first embodiment of a thermally conductive sheet. [Diagram 2] FIG. 2 is a schematic perspective view showing a scaly filler. [Diagram 3] FIG. 2 is a schematic perspective view showing an example of a method for producing a thermally conductive sheet. [Figure 4] FIG. 2 is a schematic perspective view showing a second embodiment of a thermally conductive sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the thermally conductive sheet according to an embodiment of the present invention will be described in detail. [First embodiment] FIG. 1 is a schematic diagram of a thermally conductive sheet 10 according to a first embodiment, and FIG. 2 is a schematic diagram for explaining the details of a scale-like filler 12. The thermally conductive sheet 10 according to the first embodiment includes a polymer matrix 11 and a scale-like filler 12 dispersed in the polymer matrix 11. As shown in FIG. 2, the length direction of the scale-like filler 12 on the scale surface is a major axis direction Y, the direction perpendicular to the major axis direction on the scale surface is a horizontal axis direction X, and the thickness direction of the scale-like filler 12 perpendicular to the major axis direction Y and the horizontal axis direction X is a thickness direction Z. The scale-like filler 12 is a thermally conductive filler that enhances the thermal conductivity of the thermally conductive sheet 10.
[0011] In the thermally conductive sheet 10, the scaly filler 12 is oriented such that its major axis direction Y is along a first direction, which is the thickness direction of the thermally conductive sheet 10, and its horizontal axis direction X is along a second direction perpendicular to the first direction. Here, the second direction is one direction in the surface direction of the sheet. Therefore, the thermally conductive sheet 10 has good thermal conductivity not only in the thickness direction but also in one direction in the surface direction of the thermally conductive sheet 10. In this specification, a direction perpendicular to both the first and second directions is defined as a third direction. The third direction is one direction along the surface direction of the thermally conductive sheet 10. The thermally conductive sheet 10 has good thermal conductivity not only in the thickness direction but also in one direction in the surface direction, which enhances the heat dissipation effect while also dissipating heat in the surface direction, making it difficult for heat spots to occur. Furthermore, since the thermal conductivity is not very high in directions other than the one direction in the surface direction, it is possible to prevent heat from being transferred in that direction, for example, when there is an element with low heat resistance on the board.
[0012] The thermally conductive sheet 10 may contain, in addition to the scaly filler 12, an anisotropic filler other than the scaly filler 12 as the thermally conductive filler dispersed in the polymer matrix 11, and specifically, as shown in Fig. 1, it is preferable that the thermally conductive sheet contains a fibrous filler 13 in addition to the scaly filler 12. By containing the fibrous filler 13 in addition to the scaly filler 12, for example, the presence of the fibrous filler 13 between the scaly fillers 12 forms a good thermal conduction path, and high thermal conductivity is obtained.
[0013] The fibrous filler 13 is oriented so that its fiber axis direction is along the first direction, which is the thickness direction of the sheet. By orienting the fibrous filler 13 along the first direction, the thermally conductive sheet 10 can further increase the thermal conductivity in the thickness direction of the sheet (first direction), and it becomes easier to make the thermal conductivity along the first direction sufficiently higher than the thermal conductivity along the second direction.
[0014] The thermally conductive sheet 10 also preferably contains a non-anisotropic filler (not shown) as the thermally conductive filler dispersed in the polymer matrix 11. By containing the non-anisotropic filler, the thermally conductive sheet 10 has a further improved thermal conductivity because a thermally conductive filler is appropriately interposed between the anisotropic fillers such as the scaly filler 12. In this specification, an anisotropic filler is a filler that has anisotropy in shape and can be oriented. An anisotropic filler usually has an aspect ratio greater than 2. A non-anisotropic filler is a filler that does not have substantial anisotropy in shape, and is a filler that does not orient in a specific direction even under an environment in which an anisotropic filler is oriented in a specific direction, such as under the action of a shear force described later. As described later, a non-anisotropic filler is, for example, one whose aspect ratio is 2 or less.
[0015] In the present invention, as the thermally conductive filler contained in the polymer matrix 11, the scaly filler 12 may be used alone, or both the scaly filler 12 and the fibrous filler 13 may be used, or the scaly filler 12 may be used in combination with a non-anisotropic filler. Furthermore, the scaly filler 12, the fibrous filler 13 and the non-anisotropic filler may be used in combination.
[0016] Hereinafter, each material constituting the thermally conductive sheet according to this embodiment will be described in more detail. (polymer matrix) The polymer matrix 11 is a member that holds a thermally conductive filler such as the scale-like filler 12, and is preferably made of a soft rubber-like elastic body. The polymer matrix is formed from a resin that is its precursor. Note that the precursor in this specification is a concept that includes not only a substance that becomes the polymer matrix 11 by reacting as described below, but also a substance that does not react and is the same as the polymer matrix 11. In order to incorporate an anisotropic filler such as the scale-like filler 12 in an oriented state into the polymer matrix 11, the resin is required to have fluidity during the orientation process. For example, if the resin that is the precursor of the polymer matrix 11 is a thermoplastic resin, the anisotropic filler can be oriented in a heated and plasticized state. In addition, if a reactive liquid resin is used, the anisotropic filler can be oriented before curing and then cured while maintaining that state to obtain a cured product in which the anisotropic filler is oriented. Thermoplastic resins have a relatively high viscosity, and if plasticized to a low viscosity, the resin may be thermally deteriorated, so it is preferable to use a reactive liquid resin.
[0017] As the reactive liquid resin, it is preferable to use a rubber or gel that is liquid before the reaction and hardens under a predetermined condition to form a crosslinked structure. The crosslinked structure refers to a structure in which at least a part of the polymer is crosslinked three-dimensionally to form a hardened body that does not melt when heated. In addition, since a mixed composition is prepared by adding an anisotropic filler to a liquid resin and these are oriented in the liquid resin with fluidity, it is preferable that the viscosity is low and that the resin has the property of being hardened under a predetermined condition after orientation.
[0018] Examples of the curing method of such reactive liquid resins include thermosetting and photosetting, but since they contain a large amount of filler such as a scaly filler that blocks light, it is preferable to use thermosetting rubber or gel. More specifically, examples include silicone resin, urethane rubber that utilizes the reaction of polyol and isocyanate, and acrylic rubber that utilizes the radical reaction or cationic reaction of acrylate, but it is preferable to use silicone resin.
[0019] Silicone resin is not particularly limited as long as it is organopolysiloxane, but it is preferable to use curable silicone resin. When silicone resin is curable, it is obtained by curing a curable silicone composition. Silicone resin may be an addition reaction type or other types may be used. When silicone resin is an addition reaction type, it is preferable that curable silicone composition is composed of a silicone compound as a main component and a curing agent that cures the main component.
[0020] The silicone compound used as the base agent is preferably an alkenyl group-containing organopolysiloxane, and specific examples include vinyl group-containing organopolysiloxanes such as vinyl group-containing polydimethylsiloxane, vinyl group-containing polyphenylmethylsiloxane, vinyl group-containing dimethylsiloxane-diphenylsiloxane copolymer, vinyl group-containing dimethylsiloxane-phenylmethylsiloxane copolymer, and vinyl group-containing dimethylsiloxane-diethylsiloxane copolymer.
[0021] The curing agent is not particularly limited as long as it can cure the silicone compound, which is the main component, but organohydrogenpolysiloxane, which is an organopolysiloxane having two or more hydrosilyl groups (SiH), is preferred. The hardness of the primary sheet, which will be described later, can be adjusted by appropriately adjusting the number of hydrosilyl groups, the molecular weight, and the blending ratio of the curing agent to the base agent. Specifically, the hardness of the primary sheet can be reduced by using a curing agent with fewer hydrosilyl groups per molecule or a large molecular weight, or by reducing the blending ratio of the curing agent to the base agent.
[0022] The content of the polymer matrix in the thermally conductive sheet, expressed in volume % (filling rate), is preferably 15 to 50 volume %, and more preferably 20 to 45 volume %, based on the total volume of the thermally conductive sheet.
[0023] (scaly filler) It is preferable that the scaly filler 12 has a first aspect ratio, expressed as the ratio of the length in the long axis direction Y to the length in the horizontal axis direction X (length in the long axis direction Y / length in the horizontal axis direction X), of 1.5 or more. By setting the first aspect ratio to 1.5 or more, the thermal conductivity in the first direction (thickness direction) can be made significantly higher than the thermal conductivity in the second direction (one direction of the surface direction). This prevents heat from being transferred in the surface direction more than necessary, while increasing the thermal conductivity in the thickness direction, making it easier to improve the heat dissipation effect. In addition, from the viewpoint of making the thermal conductivity in the first direction (thickness direction) sufficiently higher than the thermal conductivity along the surface direction, the first aspect ratio is more preferably 1.7 or more. However, the first aspect ratio need only be 1 or greater. If the first aspect ratio is, for example, less than 1.5, it becomes difficult to achieve a significant difference in thermal conductivity between the first direction and the second direction, but it is suitable for applications requiring high thermal conductivity in both the thickness direction and the surface direction. The first aspect ratio is, for example, 5 or less, preferably 3 or less, and more preferably 2.5 or less, in order to impart a certain level of thermal conductivity in the second direction as well.
[0024] From the viewpoint of easily orienting the scaly filler 12 in the first direction (thickness direction) and enhancing thermal conductivity, the second aspect ratio, which is expressed as the ratio of the length in the long axis direction Y to the length in the thickness direction Z (length in the long axis direction Y / length in the thickness direction Z), is preferably 3 or more, and more preferably 6 to 300. In order to reduce the viscosity of the mixture in which the materials are blended, the second aspect ratio is more preferably 8 to 15, while from the viewpoint of preventing the scaly filler 12 from falling off from the cured product and enhancing thermal conductivity, the second aspect ratio is more preferably 15 to 300. The second aspect ratio is usually larger than the first aspect ratio.
[0025] Moreover, the average particle size of the scaly filler 12 is preferably 20 μm or more. The average particle size is the average of the length of the long axis direction Y. When the average particle size is 20 μm or more, the scaly filler 12 is easily oriented along the first direction (thickness direction), and the fillers are easily brought into contact with each other, so that a heat transfer path is secured and thermal conductivity, particularly thermal conductivity in the first direction, is easily improved. From the viewpoint of improving thermal conductivity, the average particle size of the scaly filler 12 is more preferably 30 μm or more, even more preferably 40 μm or more, and even more preferably 60 μm or more. In addition, from the viewpoint of reducing the bulk of the scaly filler 12 and making it easier to highly fill the polymer matrix 11, the average particle size of the scaly filler 12 is preferably 400 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, and even more preferably 150 μm or less. The scaly filler 12 may be used alone or in combination of two or more kinds. For example, the scaly filler 12 may have at least two different average particle sizes.
[0026] The aspect ratio (first and second aspect ratios) and average particle size of the scaly filler 12 can be obtained by observing the scaly filler 12 with a microscope and measuring each length. For example, the matrix component of the thermally conductive sheet 10 is dissolved to separate the scaly filler 12, and the length of the major axis direction of 50 random scaly fillers 12 is measured with an electron microscope or an optical microscope, and the average value (arithmetic mean value) of the measured values can be regarded as the average particle size. At this time, a large shear is not applied so as not to crush the scaly filler 12. In addition, when it is difficult to separate the scaly filler 12 from the thermally conductive sheet 10, the length of the major axis direction Y of the scaly filler 12 can be measured with an X-ray CT device, and the average value (arithmetic mean value) of the measured values can be regarded as the average particle size. Similarly, the length in the longitudinal direction Y, the length in the transverse direction X, and the length in the thickness direction Z (i.e., the thickness) of any 50 pieces of scaly filler 12 can be measured, and the first and second aspect ratios can be calculated from the ratio of the average values (arithmetic mean values). In this specification, "arbitrary" refers to something selected at random.
[0027] Examples of the scaly filler 12 include scaly carbon powder, scaly silicon carbide powder, scaly aluminum nitride powder, scaly boron nitride powder, and scaly aluminum oxide powder. Among them, from the viewpoint of thermal conductivity, at least one selected from scaly graphite powder and scaly boron nitride powder is preferable. Moreover, from the viewpoint of improving thermal conductivity, particularly thermal conductivity in the first direction, the scaly filler 12 is more preferably scaly graphite powder. In flake graphite powder, the crystal planes of graphite are aligned in the in-plane direction of the flake surface, and the flake surface has high thermal conductivity in the in-plane direction. Therefore, by aligning the flake surface in a specific direction, the thermal conductivity in a specific direction can be increased. The flake graphite powder preferably has a high degree of graphitization.
[0028] The content of the scaly filler 12 in the thermally conductive sheet 10 is preferably 8 to 400 parts by mass relative to 100 parts by mass of the polymer matrix. By making the content of the scaly filler 12 8 parts by mass or more, the thermal conductivity in the first and second directions is easily increased, and by making the content of the scaly filler 12 400 parts by mass or less, the viscosity of the liquid composition described below is easily appropriate, and the orientation of the scaly filler 12 is good. From these viewpoints, the content of the scaly filler 12 in the thermally conductive sheet 10 is more preferably 40 to 300 parts by mass, and even more preferably 70 to 200 parts by mass. Moreover, the content of the scaly filler 12, expressed as a filling rate based on volume (volume filling rate), is preferably 5 to 50 volume %, more preferably 8 to 40 volume %, and even more preferably 13 to 30 volume % relative to the total amount of the thermally conductive sheet. As described above, the thermally conductive sheet 10 may be used in combination with other anisotropic fillers such as fibrous filler 13. When the scale-like filler 12 is used in combination with the fibrous filler 13, the preferred total amount of the scale-like filler 12 and the fibrous filler 13 is as described below.
[0029] As described above, the scaly filler 12 is oriented such that the major axis direction Y is aligned along the first direction of the thermally conductive sheet 10 and the horizontal axis direction X is aligned along the second direction of the thermally conductive sheet 10. Here, the long axis direction Y being along the first direction means that the proportion of the number of flake-like fillers 12 whose angle (orientation angle) between the long axis direction Y and the first direction of the thermally conductive sheet 10 is less than 30° exceeds 50% with respect to the total amount of flake-like fillers, and this proportion preferably exceeds 80%. In addition, the horizontal axis direction X being along the second direction means that the proportion of the number of flake-like fillers 12 whose angle with respect to the second direction of the thermally conductive sheet 10 of the horizontal axis direction X is less than 30° exceeds 50% with respect to the total amount of the flake-like fillers, and this proportion preferably exceeds 80%. In addition, from the viewpoint of increasing the thermal conductivity in the first direction, it is preferable that the angle (orientation angle) between the long axis direction Y of the scaly filler 12 and the first direction is greater than or equal to 0° and less than 30°, and this angle is the average value of the orientation angles of a certain number of scaly fillers 12 (for example, 50 arbitrary scaly fillers 12). Furthermore, from the viewpoint of increasing the thermal conductivity in the second direction, it is preferable that the angle that the horizontal axis direction X of the scaly filler 12 makes with respect to the second direction be greater than or equal to 0° and less than 30°, and this angle is the average value of the angles made by a certain number of scaly fillers 12 (for example, 50 arbitrary scaly fillers 12).
[0030] (fibrous filler) As described above, the thermally conductive sheet 10 preferably contains the fibrous filler 13 dispersed in the polymer matrix 11. From the viewpoint of enhancing thermal conductivity by facilitating orientation of the fiber axis direction in the first direction, the aspect ratio of the fibrous filler 13 is preferably 4 or more, more preferably 7 to 100, and even more preferably 15 to 50. The aspect ratio means the length in the fiber axis direction of the fibrous filler 13 (fiber length) / fiber diameter.
[0031] In this embodiment, the first aspect ratio of the scaly filler 12 and the aspect ratio of the fibrous filler 13 can be said to be the ratio of the length of the anisotropic filler in the first direction to the length of the anisotropic filler in the second direction. Therefore, the weighted average of the first aspect ratio of the scaly filler 12 and the aspect ratio of the fibrous filler 13 (also referred to as the "first direction / second direction aspect ratio") can be considered to be a ratio indicating the extent to which the anisotropic filler is oriented in the first direction relative to the second direction. The weighted average value of the aspect ratio is the average value obtained by weighting the aspect ratio of each anisotropic filler (the first aspect ratio for the scaly filler 12, and the aspect ratio for the fibrous filler 13) by the amount of blending (volume ratio). Specifically, the aspect ratio of the first direction / second direction may be 1 or more, but is preferably 1.5 or more, more preferably 1.7 or more, and even more preferably 3 or more. When this aspect ratio is 1.5 or more, in this embodiment, the thermal conductivity in the thickness direction is high, and the heat dissipation effect is high when used in electronic devices, etc. In addition, the aspect ratio of the first direction / second direction is preferably, for example, 8 or less, more preferably 7 or less, and even more preferably 5 or less. When this aspect ratio is 8 or less, in this embodiment, the thermal conductivity in the surface direction is high, making it easier to prevent heat spots, etc.
[0032] The average fiber length of the fibrous filler 13 is preferably 20 to 500 μm, more preferably 80 to 400 μm. When the average fiber length is 20 μm or more, the fillers in the thermally conductive sheet are in proper contact with each other, a heat transfer path is ensured, and the thermal conductivity of the thermally conductive sheet 10 is improved. On the other hand, when the average fiber length is 500 μm or less, the bulk of the fibrous filler 13 is reduced, allowing for high packing. In addition, even if a conductive fibrous filler is used as the fibrous filler 13, the conductivity of the thermally conductive sheet 10 is prevented from becoming higher than necessary. The average fiber length can be calculated by observing the fibrous filler 13 under a microscope. For example, the fiber lengths of 50 pieces of the fibrous filler 13 separated by dissolving the matrix component of the thermally conductive sheet 10 can be measured using an electron microscope or an optical microscope, and the average value (arithmetic mean value) can be used as the average fiber length. At this time, a large shear is not applied so as not to crush the fibers. In addition, if it is difficult to separate the fibrous filler 13 from the thermally conductive sheet 10, the fiber length of the fibrous filler 13 can be measured using an X-ray CT device, and the average fiber length can be calculated. Similarly, the diameter of the fibrous filler 13 can be measured using an electron microscope, an optical microscope, or an X-ray CT device.
[0033] Examples of the fibrous filler 13 include carbon fiber, metal fiber, ceramic fiber, polyparaphenylene benzoxazole fiber, etc. Among these, carbon fiber is preferable. As the carbon fiber, graphitized carbon fiber is preferable. In graphitized carbon fiber, the crystal planes of graphite are arranged in the fiber axis direction, and the graphitized carbon fiber has high thermal conductivity in the fiber axis direction. Therefore, by aligning the fiber axis direction in a specific direction, the thermal conductivity in a specific direction can be increased. As the graphitized carbon fiber, one having a high degree of graphitization is preferable.
[0034] As the graphitized carbon material such as the graphitized carbon fiber described above, the following raw materials can be graphitized. For example, condensed polycyclic hydrocarbon compounds such as naphthalene, condensed heterocyclic compounds such as PAN (polyacrylonitrile) and pitch can be mentioned, but it is preferable to use graphitized mesophase pitch, polyimide, and polybenzazole, which have a particularly high degree of graphitization. For example, by using mesophase pitch, the pitch is oriented in the fiber axis direction due to its anisotropy in the spinning process described later, and graphitized carbon fiber having excellent thermal conductivity in the fiber axis direction can be obtained. The use of mesophase pitch in graphitized carbon fiber is not particularly limited as long as it can be spun, and mesophase pitch may be used alone or in combination with other raw materials. However, it is most preferable to use mesophase pitch alone, that is, graphitized carbon fiber containing 100% mesophase pitch, from the viewpoints of high thermal conductivity, spinnability, and stability of quality.
[0035] The graphitized carbon fiber may be one which has been subjected to spinning, infusibility and carbonization in sequence, pulverized or cut to a predetermined particle size, and then graphitized, or one which has been pulverized or cut after carbonization and then graphitized. When pulverization or cutting is performed before graphitization, the newly exposed surface due to pulverization is more likely to undergo condensation polymerization and cyclization reactions during the graphitization process, and therefore it is possible to obtain graphitized carbon fiber with a higher degree of graphitization and further improved thermal conductivity. On the other hand, when spun carbon fiber is graphitized and then pulverized, the graphitized carbon fiber is easy to pulverize because it is hard, and carbon fiber powder with a relatively narrow fiber length distribution can be obtained by pulverization for a short period of time. The fibrous filler 13 may be used alone or in combination of two or more kinds. For example, as the fibrous filler 13, at least two fillers having different average fiber lengths may be used.
[0036] As described above, the fiber axis direction of the fibrous filler 13 is oriented along the first direction. Here, the fiber axis direction along the first direction means that the ratio of the number of fibrous fillers 13 whose major axes form an angle of less than 30° with respect to the first direction exceeds 50% with respect to the total amount of fibrous fillers, and this ratio is preferably more than 80%. In addition, from the viewpoint of increasing thermal conductivity, it is preferable that the orientation direction of the fibrous filler 13 is such that the angle (orientation angle) between the fiber axis direction of the fibrous filler 13 and the first direction is greater than or equal to 0° and less than 5°, and this angle is the average value of the orientation angles of a certain number of fibrous fillers 13 (for example, 50 pieces of any fibrous filler 13).
[0037] When the scaly filler 12 and the fibrous filler 13 are contained, the mass ratio of the scaly filler 12 to the fibrous filler 13 (scaly filler / fibrous filler) is preferably 20 / 80 to 95 / 5, more preferably 30 / 70 to 90 / 10, and further preferably 55 / 45 to 80 / 20. By making the mass ratio 20 / 80 or more, the amount of the scaly filler 12 can be made constant or more, and it becomes easier to improve the thermal conductivity not only in the first direction but also in the second direction. In addition, by making the mass ratio 95 / 5 or less, it becomes easier to exert the effect of containing the fibrous filler 13, and it becomes easier to improve the thermal conductivity in the first direction, for example.
[0038] The total content of the scaly filler 12 and the fibrous filler 13 in the thermally conductive sheet 10 is preferably 10 to 500 parts by mass relative to 100 parts by mass of the polymer matrix. By making the total content 10 parts by mass or more, it becomes easier to increase the thermal conductivity, and by making it 500 parts by mass or less, it becomes easier to make the viscosity of the liquid composition described below appropriate, resulting in good orientation of each filler. From these viewpoints, the total content of the scaly filler 12 and the fibrous filler 13 in the thermally conductive sheet 10 is more preferably 50 to 350 parts by mass, and even more preferably 80 to 250 parts by mass. Moreover, the total content, expressed as a filling rate on a volume basis (volume filling rate), is preferably 2 to 50 volume %, more preferably 8 to 40 volume %, and even more preferably 15 to 30 volume % with respect to the total amount of the thermally conductive sheet.
[0039] The thermal conductivity of the scaly filler 12 and the fibrous filler 13 along the anisotropic direction (i.e., the long axis direction, the fiber axis direction) is generally, but not limited to, 30 W / (m·K) or more, and preferably 100 W / (m·K) or more. The upper limit of the thermal conductivity is not particularly limited, but is, for example, 2000 W / (m·K) or less. The method for measuring the thermal conductivity is the laser flash method. Furthermore, the scaly filler 12 and the fibrous filler 13 may be conductive or insulating. When the scaly filler 12 and the fibrous filler 13 are insulating, the insulation in the thickness direction of the thermal conductive sheet 10 can be increased in this embodiment, making it possible to suitably use the thermal conductive sheet in electrical devices. In the present invention, being conductive means, for example, a filler having a volume resistivity of 1×10 9 In addition, insulation means a material with a volume resistivity of, for example, 1×10 9 This refers to a resistance exceeding Ω·cm.
[0040] (non-anisotropic filler) As described above, the thermally conductive sheet 10 preferably contains a non-anisotropic filler (not shown) in the polymer matrix 11. The non-anisotropic filler is a material that imparts thermal conductivity to the thermally conductive sheet 10 together with anisotropic fillers such as the scaly fillers 12. By including a non-anisotropic filler, the filler is interposed between the oriented anisotropic fillers such as the scaly fillers 12, and a thermally conductive sheet with higher thermal conductivity can be obtained. A non-anisotropic filler is a filler that has substantially no anisotropy in shape, and is a filler that does not orient in a specified direction even in an environment in which an anisotropic filler such as the scaly filler 12 orients in a specified direction, such as under the action of shear force described below.
[0041] The aspect ratio of the non-anisotropic filler is preferably less than 2, and more preferably not more than 1.5. By making the aspect ratio less than 2, it is possible to prevent the viscosity of the liquid composition described below from increasing, and to achieve high filling.
[0042] The non-anisotropic filler may be conductive, but is preferably insulating, and in the thermally conductive sheet 10, the fillers (i.e., the scaly filler 12, or the scaly filler 12 and the fibrous filler 13, and the non-anisotropic filler) blended therein are preferably insulating. If these are insulating, then in this embodiment, it is easier to increase the insulation in the thickness direction of the thermally conductive sheet 10.
[0043] Examples of the non-anisotropic filler include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides other than metals, etc. Examples of the shape of the non-anisotropic filler include spherical and amorphous powders. In the non-anisotropic filler, examples of metals include aluminum, copper, nickel, etc., examples of metal oxides include aluminum oxide, magnesium oxide, zinc oxide, etc., such as alumina, and examples of metal nitrides include aluminum nitride. Examples of metal hydroxides include aluminum hydroxide. Furthermore, examples of carbon materials include spherical graphite. Examples of oxides, nitrides, and carbides other than metals include quartz, boron nitride, and silicon carbide. Among the above, examples of non-anisotropic fillers having insulating properties include metal oxides, metal nitrides, metal hydroxides, and metal carbides. Among the above-mentioned non-anisotropic fillers, aluminum oxide and aluminum are preferred because they have high thermal conductivity and are easily available in spherical form, while aluminum hydroxide is preferred because it is easily available and can increase the flame retardancy of the thermal conductive sheet. Of these, aluminum oxide is more preferred.
[0044] The average particle size of the non-anisotropic filler is preferably 0.1 to 50 μm, more preferably 0.5 to 35 μm. Also, it is particularly preferably 1 to 20 μm. By making the average particle size 50 μm or less, problems such as disturbing the orientation of an anisotropic filler such as a scaly filler are unlikely to occur. Also, by making the average particle size 0.1 μm or more, the specific surface area of the non-anisotropic filler does not become larger than necessary, and even if a large amount is blended, the viscosity of the liquid composition is unlikely to increase, making it easy to highly fill the non-anisotropic filler. The average particle size of the non-anisotropic filler can be measured by observation using an electron microscope, etc. More specifically, like the measurements of the scaly filler 12 and the fibrous filler 13, the particle sizes of 50 arbitrary non-anisotropic fillers can be measured using an electron microscope, optical microscope, or X-ray CT device, and the average value (arithmetic mean value) can be regarded as the average particle size. The non-anisotropic filler may be used alone or in combination of two or more. When two or more types of each filler are used, the average particle size of each filler is calculated without distinguishing between them.
[0045] The content of the non-anisotropic filler in the thermally conductive sheet 10 is preferably in the range of 50 to 1500 parts by mass, more preferably in the range of 200 to 800 parts by mass, and even more preferably in the range of 250 to 550 parts by mass, relative to 100 parts by mass of the polymer matrix. By making it 50 parts by mass or more, the amount of the non-anisotropic filler present in the gaps of the anisotropic filler such as the scaly filler 12 becomes a certain amount or more, and the thermal conductivity becomes good. On the other hand, by making it 1500 parts by mass or less, it is possible to obtain an effect of increasing the thermal conductivity according to the content, and the non-anisotropic filler does not inhibit the thermal conduction by the anisotropic filler such as the scaly filler 12. In addition, by making it in the range of 200 to 800 parts by mass, the thermal conductivity of the thermally conductive sheet 10 is excellent, and the viscosity of the liquid composition is also suitable. The content of the non-anisotropic filler, expressed in volume %, is preferably 10 to 75 volume %, more preferably 30 to 60 volume %, and even more preferably 35 to 50 volume %, based on the total volume of the thermally conductive sheet.
[0046] (Additional ingredients) In the thermally conductive sheet 10, various additives may be further blended into the polymer matrix 11 within a range that does not impair the function of the thermally conductive sheet 10. Examples of the additives include at least one selected from dispersants, coupling agents, adhesives, flame retardants, antioxidants, colorants, and anti-settling agents. In addition, when curing the curable silicone composition as described above, a curing catalyst that accelerates curing may be blended as an additive. Examples of the curing catalyst include platinum-based catalysts.
[0047] [Unit Layer] The thermally conductive sheet 10 is manufactured by, but is not limited to, a manufacturing method described below, and is composed of a plurality of unit layers 14. Each unit layer 14 in the thermally conductive sheet 10 contains a scale-like filler 12. As shown in FIG. 1, the plurality of unit layers 14 are stacked along a third direction, and adjacent unit layers 14 are bonded to each other.
[0048] Each unit layer 14 may contain only the scaly filler 12 as the thermally conductive filler, or may contain both the scaly filler 12 and the fibrous filler 13, or may contain the scaly filler 12 and a non-anisotropic filler (not shown in FIG. 1).Furthermore, it may contain the scaly filler 12, the fibrous filler 13, and a non-anisotropic filler. Moreover, each unit layer 14 has substantially the same composition. Therefore, the contents of the scale-like filler 12, the fibrous filler 13, the non-anisotropic filler, and the polymer matrix in each unit layer 14 are the same as those in the thermally conductive sheet, and the contents and filling rates of the scale-like filler 12, the fibrous filler 13, the non-anisotropic filler, and the polymer matrix 11 in each unit layer 14 are also as described above.
[0049] In each unit layer 14, the scale-like filler 12 is oriented such that the long axis direction Y is along the first direction and the horizontal axis direction X is along the second direction, as described above. When the thermally conductive sheet 10 contains a fibrous filler 13, the fibrous filler 13 is oriented in each unit layer 14 such that the fiber axis direction is along the first direction. In each unit layer 14, the polymer matrix 11 is a component that holds the thermally conductive filler described above, and in each unit layer 14, the polymer matrix 11 is blended so that the thermally conductive fillers described above are dispersed therein.
[0050] (Thermal Conductivity) The thermal conductivity of the thermally conductive sheet 10 in the first direction is, for example, 5 W / (m·K) or more, preferably 8 W / (m·K) or more, and more preferably 11 W / (m·K) or more. By making the thermal conductivity equal to or greater than these lower limits, the thermal conductivity of the thermally conductive sheet 10 in the thickness direction can be made excellent. There is no particular upper limit, but the thermal conductivity of the thermally conductive sheet 10 in the thickness direction is, for example, 50 W / (m·K) or less. The thermal conductivity is measured by a method conforming to ASTM D5470-06.
[0051] The scaly filler 12 is oriented such that its horizontal axis direction X is along the second direction. Therefore, high thermal conductivity is also exhibited in the second direction. The thermal conductivity of the thermally conductive sheet 10 in the second direction is preferably 2.5 W / (m·K) or more, more preferably 3 W / (m·K) or more, and even more preferably 4.5 W / (m·K) or more. There is no upper limit to the thermal conductivity of the thermally conductive sheet 10 in the second direction, but it is, for example, 50 W / (m·K) or less.
[0052] Furthermore, with the thermally conductive sheet 10, the scaly filler 12 is oriented as described above, so that the thermal conductivity in the third direction (the direction perpendicular to the second direction along the surface direction) is lower than the thermal conductivity in the first and second directions. The thermal conductivity of the thermally conductive sheet 10 in the third direction is preferably less than 4.5 W / (m·K), more preferably less than 3 W / (m·K), and even more preferably less than 2.5 W / (m·K). The lower limit of the thermal conductivity of the thermally conductive sheet 10 in the third direction is not particularly limited, but is, for example, 0.2 W / (m·K) or more.
[0053] Moreover, the thermal characteristic level in the second direction calculated by the following formula is preferably 10% or more. When it is 10% or more, the thermally conductive sheet 10 has anisotropy of thermal conductivity in the surface direction, and can transfer heat in one surface direction while preventing heat transfer in the other direction. From this viewpoint, the thermal characteristic level in the second direction is more preferably 20% or more, and even more preferably 50% or more. Furthermore, the thermal characteristic level in the second direction may be 100% or less, but from the viewpoint of improving the thermal conductivity in the thickness direction more than the thermal conductivity in the surface direction to provide excellent heat dissipation, it is preferably 90% or less, and more preferably 80% or less. Thermal property level in the second direction (%) = (λ2-λ3) / (λ1-λ3)×100 λ1: Thermal conductivity in the first direction λ2: Thermal conductivity in the second direction λ3: Thermal conductivity in the third direction
[0054] The thermally conductive sheet 10 has a Type E hardness of, for example, not more than 70. When the thermally conductive sheet 10 has a Type E hardness of not more than 70, flexibility is ensured, and, for example, conformability to a heat generating body and a heat dissipating body is improved, and heat dissipation properties are likely to be improved. Furthermore, when used on an adherend with large irregularities, it is preferable that the thermally conductive sheet 10 is extremely flexible, and the type OO hardness of the thermally conductive sheet 10 is preferably 62 or less. When the type OO hardness of the thermally conductive sheet 10 is 62 or less, the thermally conductive sheet 10 becomes an extremely flexible thermally conductive sheet, and has extremely good conformability to heat generating bodies and heat dissipating bodies. From the viewpoint of improving flexibility and making conformability excellent, the type OO hardness of the thermally conductive sheet 10 is preferably 50 or less, more preferably 45 or less. On the other hand, the type OO hardness of the thermally conductive sheet 10 is not particularly limited, but is, for example, 15 or more, preferably 18 or more, more preferably 25 or more. Furthermore, when priority is given to the ease of handling of the thermally conductive sheet 10, the type E hardness of the thermally conductive sheet 10 is preferably 15 or more, and particularly preferably 35 or more. The softer the hardness of the thermally conductive sheet 10, the less stress it can exert on the heating element, the heat sink, or the substrate on which they are placed when compressed, and this is preferable, but by setting the hardness to 15 or more in type OO hardness, the thermally conductive sheet 10 can be made to have good predetermined handleability and easy to attach to the adherend. In particular, a type E hardness of 35 or more can provide an excellent balance between handleability and softness. The above type E hardness and type OO hardness are values measured using a prescribed durometer in accordance with the method specified in ASTM D2240-05.
[0055] The type OO hardness of the thermally conductive sheet 10 and the primary sheet described below was measured in accordance with the standard of ASTM D2240-05. The type OO hardness is measured by adjusting the test piece to 10 mm, measuring the hardness on both sides of the test piece, and calculating the average value. However, if the thickness is less than 10 mm, multiple sheets are stacked to adjust the thickness of the test piece to 10 mm, or to a thickness greater than 10 mm and closest to 10 mm.
[0056] In this embodiment, an anisotropic filler such as the scale-like filler 12, or the scale-like filler 12 and the fibrous filler 13 may be exposed on either of the two surfaces 10A and 10B of the thermally conductive sheet 10. The exposed scale-like filler 12, or the scale-like filler 12 and the fibrous filler 13 may protrude from each of the two surfaces 10A and 10B. The thermally conductive sheet 10 has an anisotropic filler exposed on each of the surfaces 10A and 10B, so that each of the surfaces 10A and 10B becomes a non-adhesive surface. Note that each of the two surfaces 10A and 10B of the thermally conductive sheet 10 becomes a cut surface by, for example, cutting with a blade described later, and thus the scale-like filler 12, or the scale-like filler 12 and the fibrous filler 13 are exposed on each of the two surfaces 10A and 10B. However, one or both of the surfaces 10A, 10B may be an adhesive surface without exposing the anisotropic filler.
[0057] The thickness of the thermally conductive sheet 10 is appropriately changed depending on the shape and application of the electronic device in which the thermally conductive sheet 10 is mounted. The thickness of the thermally conductive sheet 10 is not particularly limited, but may be in the range of 0.1 to 5 mm, for example.
[0058] The thickness of each unit layer 14 is not particularly limited, but is preferably 0.1 to 10.0 mm. By setting the thickness of each unit layer 14 within the above range, it becomes possible to orient the major axis direction Y and the horizontal axis direction X of the scale-like filler 12 along the first and second directions, respectively, by flow orientation, which will be described later. In addition, when a fibrous filler 13 is used, it becomes easier to orient the major axis direction of the fibrous filler 13 along the first direction. From these viewpoints, the thickness of each unit layer 14 is more preferably 0.3 to 5.0 mm, and even more preferably 0.5 to 3 mm. The thickness of the unit layer 14 is the length 14L along the third direction.
[0059] The thermally conductive sheet 10 has a compression ratio of, for example, 10 to 65%, preferably 20 to 65%, when compressed at 0.276 MPa (=40 psi). If the compression ratio is equal to or greater than these lower limits, the flexibility is increased, and it becomes easy to compress and use the sheet in an electronic device or the like. If the compression ratio is equal to or less than 65%, the unit layers 14 do not expand due to the pressure applied when stacking the unit layers 14 during the manufacture of the thermally conductive sheet 10, and the thermally conductive sheet 10 can be manufactured appropriately. From the viewpoint of further improving the flexibility, the compression ratio is more preferably 25% or more. From the viewpoint of preventing the unit layers 14 from expanding during the manufacture and improving production efficiency, the compression ratio is preferably equal to or less than 60%, more preferably equal to or less than 55%.
[0060] As described later, the thermally conductive sheet 10 can prevent the compression ratio from becoming too high and adjust it to within the above-mentioned predetermined range by bonding the primary sheets together by VUV irradiation. The compression ratio in the present invention is measured when the thermally conductive sheet 10 is compressed from a direction perpendicular to the bonding surface where the unit layers 14 are bonded together, and more specifically, the thermally conductive sheet 10 is compressed in a first direction (thickness direction). The compression ratio is a parameter that indicates the ratio of the compression amount to the initial thickness, which is expressed as "(T1-T2) / T1", where T1 is the initial thickness before compression and T2 is the thickness when compressed with a predetermined pressure. The compression ratio may be measured, for example, by cutting the thermally conductive sheet to a size of 10 mm x 10 mm and sandwiching the test piece between a base with a flat surface and a presser that presses in parallel.
[0061] The thermally conductive sheet 10 is used inside electronic devices. Specifically, the thermally conductive sheet 10 is interposed between a heat generating body and a heat sink, and transfers heat generated by the heat generating body to the heat sink by thermal conduction, and dissipates the heat from the heat sink. Here, examples of the heat generating body include various electronic components used inside the electronic device, such as a CPU, a power amplifier, and a power supply. Examples of the heat sink include a heat sink, a heat pump, and a metal housing of an electronic device. The thermally conductive sheet 10 is used, for example, with both surfaces 10A and 10B in close contact with the heat generating body and the heat sink, respectively, and compressed. As described above, the thermally conductive sheet 10 in this embodiment has high thermal conductivity in the first direction (thickness direction) and therefore has excellent heat dissipation properties, and also has a certain degree of thermal conductivity in the planar direction, which makes it easier to prevent the occurrence of heat spots, etc. Furthermore, since the thermal conductivity cannot be increased in any direction other than the one in the planar direction, it is possible to prevent heat from being transferred in that direction, for example, when an element with low heat resistance is present inside an electronic device.
[0062] <Method of manufacturing thermally conductive sheet> Next, an example of a method for producing the thermally conductive sheet 10 will be described. This manufacturing method includes a mixture preparation step of preparing a mixture containing a resin that is a precursor of a polymer matrix and at least the scaly filler 12 as a thermally conductive filler, a primary sheet preparation step of subjecting the mixture to flow orientation treatment to obtain a primary sheet while orienting anisotropic fillers such as the scaly filler 12, a lamination step of laminating the primary sheets to obtain a laminated block, and a cutting step of cutting the laminated block along the lamination direction. Each step will be described in detail below.
[0063] (Mixture preparation process) In the mixture preparation step, a mixture (liquid composition) is prepared containing a resin that is a precursor of the polymer matrix (for example, a curable silicone composition in the case of a silicone resin) and a scaly filler 12. The mixture may further contain a fibrous filler 13 and a non-anisotropic filler as appropriate, and may further contain additional components. The liquid composition is usually in the form of a slurry. The components that make up the liquid composition may be mixed using, for example, a known kneader, kneading roll, mixer, etc.
[0064] Here, the viscosity of the liquid composition is preferably 100 to 10,000 Pa·s. When the viscosity is 100 Pa·s or more, by forming the filler into a sheet shape while applying a shear force in the orientation process to flow the filler, the major axis direction Y of the scaly filler 12 is easily oriented in the flow direction (one direction in the sheet surface direction) and the horizontal axis direction X is easily oriented in the sheet surface direction and perpendicular to the flow direction (the other direction in the sheet surface direction). In addition, by setting the viscosity to 10,000 Pa·s or less, the coatability is improved. From these viewpoints, the viscosity of the liquid composition is more preferably 300 to 3,000 Pa·s, and even more preferably 400 to 2,000 Pa·s. The viscosity is measured using a rotational viscometer (Brookfield viscometer DV-E, spindle SC4-14) at a rotation speed of 1 rpm, and the measurement temperature is the temperature at the time of coating of the liquid composition.
[0065] The viscosity of the liquid composition can be adjusted by the type and amount of the thermally conductive filler described above. It can also be appropriately adjusted by each component constituting the resin. For example, when the liquid composition is a curable silicone composition, the above viscosity can be achieved by appropriately adjusting the molecular weight of each component constituting the curable silicone composition (such as an alkenyl group-containing organopolysiloxane and an organohydrogenpolysiloxane). In addition, an organic solvent may be added to the liquid composition as necessary to adjust the viscosity to the above, but it is preferable not to add an organic solvent.
[0066] (First sheet preparation process) In the primary sheet preparation step, the liquid composition is formed into a sheet while applying a shear force to obtain a primary sheet. The liquid composition may be applied to a substrate film, for example, by a coating applicator such as a bar coater or a doctor blade, or by extrusion molding or ejection from a nozzle, and such a method can apply a shear force along the coating direction (flow direction) of the liquid composition. By forming into a sheet while applying a shear force in this way, the scale-like filler 12 is oriented so that the long axis direction Y is along the flow direction (one direction in the sheet surface direction) and the horizontal axis direction X is along a direction perpendicular to the flow direction (the other direction in the sheet surface direction). In addition, when a fibrous filler is blended into the liquid composition, the fibrous filler 13 is oriented so that its fiber axis direction is along the flow direction.
[0067] Next, the liquid composition formed into a sheet is cured, dried, etc. as necessary to obtain a primary sheet. In the primary sheet, as described above, the major axis direction Y of the scale-like filler 12 is oriented in one plane direction, and the horizontal axis direction X is oriented in the other plane direction. Furthermore, when the liquid composition contains, for example, a curable silicone composition, the liquid composition is cured by curing the curable silicone composition. The liquid composition may be cured by heating, for example, at a temperature of about 50 to 150°C. The heating time is, for example, about 10 minutes to 3 hours. When a solvent is blended in the curable liquid composition, the solvent may be evaporated by heating during curing.
[0068] The thickness of the primary sheet obtained by curing is preferably in the range of 0.1 to 10 mm. By setting the thickness of the primary sheet within the above range, as described above, the anisotropic filler, particularly the scaly filler 12, can be appropriately oriented along the surface direction by shear force. Furthermore, by setting the thickness of the primary sheet to 0.1 mm or more, it can be easily peeled off from the base film. Furthermore, by setting the thickness of the primary sheet to 10 mm or less, the primary sheet is prevented from being deformed by its own weight. From these viewpoints, the thickness of the primary sheet is more preferably 0.3 to 5.0 mm, and even more preferably 0.5 to 3.0 mm.
[0069] The type OO hardness of the primary sheet is preferably 6 or more. By making it 6 or more, the primary sheet does not spread much even when pressure is applied when stacking the primary sheets, and a laminated block having a sufficient thickness can be produced. From this viewpoint, the type OO hardness of the primary sheet is more preferably 10 or more, and even more preferably 15 or more. From the viewpoint of ensuring the flexibility of the obtained thermally conductive sheet 10, the type OO hardness of the primary sheet is preferably 55 or less, more preferably 50 or less, and even more preferably 40 or less. From the viewpoint of improving the handleability of the obtained thermally conductive sheet 10, the type E hardness of the primary sheet is preferably 70 or less, and more preferably 40 or less. The type E hardness of the primary sheet is preferably 10 or more, and more preferably 30 or more.
[0070] (Lamination process) Next, the multiple primary sheets 17 obtained in the primary sheet preparation step are laminated so that the orientation directions of the anisotropic filler are the same (see Figs. 3(a) and (b)). That is, the multiple primary sheets 17 are laminated so that one direction along the long axis direction Y of the above-mentioned scaly filler 12 and the other direction along the horizontal axis direction X are aligned with each other. Then, the multiple laminated primary sheets 17 are bonded together and integrated to obtain a laminated block 18. For example, when the resin of the multiple laminated primary sheets 17 is a thermoplastic resin, the polymer matrix 11 in the primary sheets 17 is melted and fixed by press molding to form the laminated block 18. Also, a known adhesive or the like may be placed between the primary sheets 17, 17 to bond the primary sheets 17, 17 together. Furthermore, in cases where the precursor of the polymer matrix is curable, multiple semi-cured primary sheets 17 may be stacked, and after stacking, each primary sheet 17 may be fully cured, and the fully cured primary sheets 17 may be bonded to one another and integrated to form a laminated block 18.
[0071] Furthermore, when the polymer matrix is a silicone resin or the like, at least one surface of the obtained primary sheet 17 may be irradiated with VUV to activate at least one surface, and the primary sheets 17, 17 may be bonded together by the activated surface. Note that VUV stands for vacuum ultraviolet light, and refers to ultraviolet light having a wavelength of 10 to 200 nm. Examples of a light source for VUV include an excimer Xe lamp and an excimer ArF lamp.
[0072] When the primary sheet 17 contains, for example, a silicone resin (organopolysiloxane) as described above, the surface irradiated with VUV is activated when the primary sheet 17 is irradiated with VUV. As described later, the primary sheet 17 is overlapped with another primary sheet 17 so that one activated surface becomes the overlapping surface, and the primary sheets 17, 17 are firmly bonded to each other. Although the principle is not clear, it is presumed that when the silicone resin is irradiated with VUV, the C-Si bond of the organopolysiloxane changes to a Si-O bond such as Si-OH, and the primary sheets 17, 17 are firmly bonded to each other by the Si-O bond. That is, the primary sheet 17 and the primary sheet (unit layer 14, 14) are bonded to each other by the formation of a bond between the molecules of the organopolysiloxane. Also, by bonding the primary sheets 17, 17 to each other by VUV irradiation, the flexibility in the direction perpendicular to the stacking direction is not significantly impaired. Therefore, the compression ratio can be easily adjusted to fall within a predetermined range. The VUV irradiation conditions are not particularly limited as long as they can activate the surface of the primary sheet 17. For example, the integrated light amount is 5 to 100 mJ / cm 2 Preferably, the integrated light amount is 10 to 50 mJ / cm 2 It is recommended to irradiate VUV so that
[0073] Here, it is sufficient that either one of the overlapping surfaces that contact each other of the primary sheets 17 has been irradiated with VUV in advance. By irradiating one surface with VUV, adjacent primary sheets 17, 17 are bonded to each other by the activated one surface. In addition, from the viewpoint of further improving the adhesiveness, it is preferable that both of the overlapping surfaces have been irradiated with VUV. That is, as shown in FIG. 3(a), the primary sheet 17 may be overlapped so that one surface 17A that has been irradiated with VUV is in contact with another primary sheet 17, and in this case, it is preferable that the other surface 17B of the other primary sheet 17 that is in contact with the one surface 17A is also irradiated with VUV.
[0074] Although the primary sheets 17 can be bonded by simply overlapping them as described above by VUV irradiation, pressure may be applied in the lamination direction of the primary sheets 17 to bond them more firmly. The pressure should be such that the primary sheets 17 do not deform significantly, and can be applied using, for example, a roller or press. As an example, when a roller is used, the pressure is preferably 0.3 to 3 kgf / 50 mm. The laminated primary sheets 17 may be appropriately heated, for example, when applying pressure, but since the primary sheets 17 activated by VUV irradiation can be bonded without heating, it is preferable not to heat the laminated primary sheets 17. Therefore, the temperature during pressing is, for example, 0 to 50°C, and preferably about 10 to 40°C.
[0075] (cutting process) Next, as shown in FIG. 3(c), the laminated block 18 is cut by a blade 19 along the lamination direction (third direction) of the primary sheets 17 to obtain the thermally conductive sheet 10. In this case, the laminated block 18 is preferably cut in a direction perpendicular to one direction (first direction) along which the major axis direction of the scaly filler 12 runs. As the blade 19, for example, a double-edged or single-edged blade such as a razor blade or a cutter knife, a round blade, a wire blade, a saw blade, or the like can be used. The laminated block 18 is cut by the blade 19 by, for example, a method such as pushing, shearing, rotating, or sliding.
[0076] [Second embodiment] Next, a first embodiment of the present invention will be described with reference to FIG. In the first embodiment, the direction along the long axis direction Y of the scaly filler 12 was the thickness direction of the sheet (first direction). However, as shown in Figure 4, in the thermally conductive sheet 20 of this embodiment, the direction along the long axis direction Y (see Figure 2) of the scaly filler 12 is a direction (second direction) perpendicular to the thickness direction of the sheet, and the direction along the horizontal axis direction X is the thickness direction of the sheet (first direction). This is different. With this configuration, in this embodiment, as in the first embodiment, the thermal conductivity is good not only in the thickness direction but also in one direction along the surface direction perpendicular to the thickness direction. However, since the direction along the long axis direction Y of the scaly filler 12 is the second direction, the thermal conductivity in one direction along the surface direction (second direction) is higher than the thermal conductivity in the thickness direction (first direction). Therefore, the thermally conductive sheet 20 of this embodiment can be suitably used in applications requiring high thermal conductivity along the surface direction.
[0077] Regarding thermal conductivity, the thermal conductivity in the first direction is preferably 2.5 W / (m·K) or more, more preferably 3 W / (m·K) or more, even more preferably 4.5 W / (m·K) or more, and is, for example, 50 W / (m·K) or less. The thermal conductivity in the second direction is higher than the thermal conductivity in the first direction, for example, 5 W / (m·K) or more, preferably 8 W / (m·K) or more, more preferably 11 W / (m·K) or more, and for example, 50 W / (m·K) or less. The thermal conductivity in the third direction is lower than the thermal conductivity in the first direction and the second direction, and is preferably less than 4.5 W / (m K), more preferably less than 3 W / (m K), and even more preferably less than 2.5 W / (m K), and is, for example, 0.2 W / (m K) or more. Also, as described above, the thermal property level in the second direction is preferably 10% or more, but usually exceeds 100%. Furthermore, in this embodiment, the weighted average value of the first aspect ratio of the scaly filler 12 and the aspect ratio of the fibrous filler 13 can be called the aspect ratio of the second direction / first direction. Specifically, the aspect ratio of the second direction / first direction in this embodiment may be 1 or more, but is preferably 1.5 or more, more preferably 1.7 or more, even more preferably 3 or more, preferably 8 or less, more preferably 7 or less, and even more preferably 5 or less.
[0078] The thermally conductive sheet 20 in this embodiment may contain other fillers such as a fibrous filler 13 and a non-anisotropic filler, as in the first embodiment. When the fibrous filler 13 is blended, the fiber axis direction of the fibrous filler 13 may also be oriented along the second direction. In addition, the physical properties and dimensions, such as the sheet thickness, the unit layer thickness 14L, the type E hardness of the thermally conductive sheet, and the compression ratio when compressed in the thickness direction at 0.276 MPa, are as described in the first embodiment above. The other configurations in the second embodiment are also similar to those in the first embodiment above, and detailed descriptions thereof will be omitted. The method for producing the thermally conductive sheet 20 in this embodiment may be the same as that in the first embodiment, except that in the cutting step, the scaly filler 12 is cut in a direction perpendicular to the one direction along which the horizontal axis of the filler 12 runs.
[0079] In the above embodiments, the unit layers 14 in the thermally conductive sheet 20 have substantially the same composition as described above, but the composition of each unit layer 14 may be different from each other. For example, the contents of the scaly filler 12, or the scaly filler 12 and the fibrous filler 13 in each unit layer 14 do not need to be the same, and the contents of the scaly filler 12 or the fibrous filler 13 in some unit layers 14 may be different from the contents of the scaly filler 12 or the fibrous filler 13 in the other unit layers 14. Similarly, the contents of the non-anisotropic filler in some unit layers 14 may be different from the contents of the non-anisotropic filler in the other unit layers 14. Furthermore, the types of at least any of the scaly filler 12, fibrous filler 13, and non-anisotropic filler in some unit layers 14 may be different from those in the other unit layers 14. Furthermore, it is not necessary for all of the multiple unit layers 14 to contain the scaly filler 12, and some of the unit layers 14 may contain the scaly filler 12, and for example, at least one of the multiple unit layers 14 may contain the scaly filler 12. That is, in each of the above embodiments, it is not necessary for the entire region of the thermally conductive sheet 20 to contain the scaly filler 12 along one of the first and second directions, and it is sufficient for a part of the thermally conductive sheet 20 to contain the scaly filler 12 along either the first or second direction. Similarly, some of the multiple unit layers 14 may contain fibrous filler 13, and the others may not contain fibrous filler 13. Also, some of the multiple unit layers 14 may contain a non-anisotropic filler, and the others may not contain a non-anisotropic filler.
[0080] As described above, by appropriately adjusting the content and type of the scale-like filler 12 and the fibrous filler 13 in each unit layer 14, the thermal conductivity of some unit layers 14 may be made higher than the thermal conductivity of other unit layers 14. In such a case, unit layers 14 with high thermal conductivity and unit layers 14 with low thermal conductivity may be arranged alternately, but do not need to be arranged alternately.
[0081] Similarly, the electrical conductivity of some of the unit layers 14 may be lower than that of the other unit layers 14. In such a case, the unit layers 14 with high electrical conductivity and the unit layers 14 with low electrical conductivity may be arranged alternately, but do not need to be arranged alternately. By making the electrical conductivity of some of the unit layers 14 lower than that of the other unit layers 14, the electrical conductivity along the third direction (see FIG. 1) is hindered by the unit layers 14 with low electrical conductivity. Therefore, the electrical conductivity in the third direction of the entire thermally conductive sheet 20 is lowered, making it easier to ensure insulation. In order to make it easier to ensure insulation, it is preferable that the unit layers 14 with low electrical conductivity do not contain a conductive thermally conductive filler but contain an insulating thermally conductive filler.
[0082] In addition, some of the multiple unit layers 14 may be unit layers 14 with relatively high thermal conductivity, and the other part may be unit layers 14 with light transparency. The unit layers 14 with thermal conductivity are layers containing a thermally conductive filler such as a thermally conductive filler or a scaly filler 12 as described above. On the other hand, the unit layers 14 with light transparency may be layers that do not contain a thermally conductive filler. With this configuration, the entire thermally conductive sheet 20 has a certain thermal conductivity and light transparency along the thickness direction. The unit layers 14 with thermal conductivity and the unit layers 14 with light transparency may be arranged alternately, but do not need to be arranged alternately.
[0083] In addition, the orientation direction of the long axis direction Y of the scaly filler 12 of each unit layer 14 does not need to be aligned in the same direction (i.e., one of the first and second directions). That is, in the present invention, it is sufficient that the orientation direction of the long axis direction Y in at least some of the unit layers 14 is one of the first direction or the second direction, and the orientation direction of the transverse axis direction X is the other of the first direction or the second direction. For example, the first directions in each unit layer 14 may be stacked sequentially so as to be mutually inclined at 90°, or by changing at any angle.
[0084] Of course, the configuration other than the thermally conductive filler may be changed for each unit layer 14. For example, the type of polymer matrix 11 of some unit layers 14 may be changed from the type of polymer matrix 11 of other unit layers 14. Furthermore, the presence or absence of an added component in some unit layers 14, the type and amount of the added component, etc. may be made different from those of the other unit layers 14. For example, the type or amount of silicone resin or at least a portion of the type or amount of thermally conductive filler of some of the unit layers 14 may be made different from that of the other unit layers 14, thereby making the hardness (type E hardness or type OO hardness) of some of the unit layers 14 different from that of the other unit layers 14. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0086] The evaluation methods in the present examples are as follows. [Measurement of viscosity of liquid composition (mixture)] The viscosity of each liquid composition was measured using a viscometer (a rotational viscometer DV-E manufactured by BROOKFIELD) with a rotor of spindle SC4-14 at a rotation speed of 1 rpm and a measurement temperature of 25° C. The results are shown in Table 1.
[0087] [Thermal Conductivity] The thermal conductivity of the thermally conductive sheet in the thickness direction (first direction) was measured according to a method in accordance with ASTM D5470-06. The thermal conductivity in the second direction and the third direction was also measured according to a method in accordance with ASTM D5470-06. The results are shown in Table 1. The thermal conductivity in the second direction is the thermal conductivity measured on a test piece (thickness 2 mm) cut from the laminated block of each example described below so that the second direction is the thickness direction, and the thermal conductivity in the third direction is the thermal conductivity measured on the primary sheet (thickness 2 mm) of each example. The level of thermal properties in the second direction is expressed as a percentage. Specifically, it was calculated using the following formula so that the same as the first direction is "100%" and the same as the third direction is "0%". Thermal property level in the second direction (%) = (λ2-λ3) / (λ1-λ3)×100 λ1: Thermal conductivity in the first direction λ2: Thermal conductivity in the second direction λ3: Thermal conductivity in the third direction
[0088] [Type E hardness] The type E hardness was measured according to the standard of ASTM D2240-05 using 10 mm test pieces made by stacking five thermally conductive sheets and primary sheets obtained in each of the Examples and Comparative Examples. The results are shown in Table 1. [Compression ratio] The thermal conductive sheets obtained in each of the Examples and Comparative Examples were prepared into samples with an outer dimension of 10 mm x 10 mm, and the compression ratio was measured when compressed at 0.276 MPa (= 40 psi) as described in the specification. The results are shown in Table 1.
[0089] [Example 1] As a curable silicone composition, an alkenyl group-containing organopolysiloxane (base agent) and a hydrogen organopolysiloxane (curing agent) (total 100 parts by mass, volume filling rate 38% by volume), 180 parts by mass (volume filling rate 30% by volume) of boron nitride powder (average major axis length 40 μm, first aspect ratio = 1, second aspect ratio = 4 to 8, thermal conductivity 100 W / (m·K)) as a scaly filler, and 340 parts by mass (volume filling rate 32% by volume) of aluminum oxide (spherical, average particle size 3 μm, aspect ratio 1.0) as a non-anisotropic filler were mixed to obtain a slurry-like liquid composition (mixture). The viscosity of the liquid composition at 25°C was 480 Pa·s.
[0090] The liquid composition was applied in one direction on a polyethylene terephthalate (PET) substrate film at 25°C using a bar coater as an applicator. The scale-like filler was oriented such that the long axis direction X was along the application direction, and the horizontal axis direction X was along one direction of the sheet surface and perpendicular to the application direction. Next, the applied liquid composition was heated at 120°C for 0.5 hours to harden the liquid composition, thereby obtaining a primary sheet having a thickness of 2 mm.
[0091] Both sides of each of the obtained primary sheets were irradiated with a VUV irradiation device (product name Excimer MINI, manufactured by Hamamatsu Photonics) at room temperature (25°C) in the atmosphere with an integrated light dose of 20 mJ / cm on the surface of the primary sheet. 2 VUV was irradiated under the following conditions. Next, 100 of the VUV-irradiated primary sheets were stacked and pressed with a roller at a pressure of 1.6 kgf / 50 mm in an environment of 25°C to obtain a laminated block. The obtained laminated block was sliced with a cutter blade in parallel with the stacking direction and perpendicular to the direction along the long axis of the scale-like filler, to obtain a thermally conductive sheet with a thickness of each unit layer of 2 mm and a sheet thickness of 2 mm. In the thermal conductive sheet, the scaly filler was oriented such that the major axis direction was along the thickness direction (first direction) and the horizontal axis direction was along the direction perpendicular to the first direction in the sheet surface direction (second direction). This was also the case in the following examples.
[0092] Example 2 The liquid composition was prepared in the same manner as in Example 1, except that flake graphite powder (average major axis length 130 μm, first aspect ratio = 2, second aspect ratio = 6 to 13, thermal conductivity 400 W / (m K)) was used as the flake filler, and the blending amount of each filler was changed as shown in Table 1. The volumetric filling rate of the silicone resin was 38% by volume, the volumetric filling rate of the scaly filler was 23% by volume, the volumetric filling rate of the non-anisotropic filler was 39% by volume, and the viscosity of the liquid composition at 25°C was 600 Pa·s.
[0093] Example 3 The liquid composition was prepared in the same manner as in Example 1, except that flake graphite powder (average major axis length 80 μm, first aspect ratio = 1.85, second aspect ratio = 4 to 8, thermal conductivity 400 W / (m·K)) was used as the flake filler, and the blending amount of each filler was changed as shown in Table 1. The volumetric filling rate of the silicone resin and each filler was the same as in Example 2, and the viscosity of the liquid composition at 25°C was 750 Pa·s.
[0094] Example 4 The liquid composition was prepared in the same manner as in Example 1, except that flake graphite powder (average major axis length 40 μm, first aspect ratio = 1.7, second aspect ratio = 3 to 6, thermal conductivity 400 W / (m·K)) was used as the flake filler, and the blending amount of each filler was changed as shown in Table 1. The volume filling rate of the silicone resin and each filler was the same as in Example 2, and the viscosity of the liquid composition at 25°C was 940 Pa·s.
[0095] Example 5 The liquid composition was prepared in the same manner as in Example 4, except that graphitized carbon fibers (average fiber length 100 μm, aspect ratio 10, thermal conductivity 500 W / (m K)) were further blended as a fibrous filler, and the blending amount of each filler was changed as shown in Table 1. The fibrous filler was oriented so that the fiber axis direction was aligned along the thickness direction (first direction), and the same was true in the following examples and comparative examples. The volume filling rate of the silicone resin was 38% by volume, the volume filling rate of the scaly filler was 9% by volume, the volume filling rate of the fibrous filler was 14% by volume, the volume filling rate of the non-anisotropic filler was 39% by volume, and the viscosity of the liquid composition at 25°C was 750 Pa s.
[0096] Example 6 The liquid composition was prepared in the same manner as in Example 5, except that the blended amount of each filler was changed as shown in Table 1. The volumetric filling rate of the silicone resin was 38% by volume, the volumetric filling rate of the scaly filler was 14% by volume, the volumetric filling rate of the fibrous filler was 9% by volume, the volumetric filling rate of the non-anisotropic filler was 39% by volume, and the viscosity of the liquid composition at 25°C was 540 Pa s.
[0097] Example 7 The liquid composition was prepared in the same manner as in Example 4, except that the blending amount of each filler was changed as shown in Table 1. The volumetric filling rate of the silicone resin was 38% by volume, the volumetric filling rate of the scaly filler was 22% by volume, the volumetric filling rate of the non-anisotropic filler was 40% by volume, and the viscosity of the liquid composition at 25°C was 960 Pa s.
[0098] Comparative Example 1 The liquid composition was prepared in the same manner as in Example 1, except that no scaly filler was used and the blended amounts of each filler were changed as shown in Table 1. The volumetric filling rate of the silicone resin was 37% by volume, the volumetric filling rate of the fibrous filler was 20% by volume, the volumetric filling rate of the non-anisotropic filler was 43% by volume, and the viscosity of the liquid composition at 25°C was 360 Pa s.
[0099] Comparative Example 2 The liquid composition was prepared in the same manner as in Example 1, except that no scaly filler was used and the blended amount of each filler was changed as shown in Table 1. The volumetric filling rate of the silicone resin was 38% by volume, the volumetric filling rate of the fibrous filler was 22% by volume, the volumetric filling rate of the non-anisotropic filler was 40% by volume, and the viscosity of the liquid composition at 25°C was 450 Pa s.
[0100] [Table 1]
[0101] In the thermally conductive sheets of the above examples, the thermal conductivity was improved not only in the thickness direction (first direction) but also in one direction along the surface direction (second direction) by including a scaly filler and orienting the scaly filler in the longitudinal direction Y along the first direction and the transverse direction X along the second direction. Therefore, the thermal conductivity in the thickness direction and in one direction along the surface direction was improved, and the thermal resistance in these directions was reduced. In contrast, the thermal conductive sheets of the comparative examples did not contain a scaly filler with the longitudinal axis direction Y oriented along the first direction and the transverse axis direction X oriented along the second direction, so that the thermal conductivity in both the thickness direction and one direction along the surface direction was not improved, and therefore the thermal resistance values in both the thickness direction and one direction along the surface direction could not be reduced. [Explanation of symbols]
[0102] 10,20 Thermally conductive sheet 10A One side 10B The other side 11 Polymer matrix 12 Scaly filler 13 Fibrous fillers 14 Unit Layer 17 1st sheet 18 Laminated Blocks 19 Knives
Claims
1. A thermally conductive sheet containing a scale-like filler in a polymer matrix, A thermally conductive sheet in which the long axis direction of the scale-like filler surface is oriented along either a first direction, which is the thickness direction of the thermally conductive sheet, or a second direction perpendicular to the first direction, and the horizontal axis direction perpendicular to the long axis direction on the scale surface is oriented along the other of the first direction and the second direction.
2. The thermally conductive sheet according to claim 1 , wherein the scale-like filler is oriented such that the major axis direction is aligned along the first direction and the horizontal axis direction is aligned along the second direction.
3. The thermally conductive sheet according to claim 1 , wherein the scaly filler is oriented such that the horizontal axis direction is aligned along the first direction and the major axis direction is aligned along the second direction.
4. A thermally conductive sheet according to any one of claims 1 to 3, wherein a first aspect ratio, expressed as the ratio of the length of the long axis direction to the length of the horizontal axis direction of the scaly filler (length of the long axis direction / length of the horizontal axis direction), is 1.5 or more.
5. The thermally conductive sheet according to any one of claims 1 to 4, wherein the average particle size of the scaly filler is 20 µm or more.
6. The thermally conductive sheet according to any one of claims 1 to 5, wherein the scaly filler contains scaly graphite powder.
7. The thermally conductive sheet according to any one of claims 1 to 6, wherein the scaly filler contains scaly boron nitride powder.
8. The thermally conductive sheet according to any one of claims 1 to 7, further comprising a fibrous filler in the polymer matrix.
9. The thermally conductive sheet according to claim 8 , wherein the fibrous filler is carbon fiber.
10. The laminate has a plurality of unit layers, and at least one of the plurality of unit layers includes the scaly filler, The thermally conductive sheet according to any one of claims 1 to 9, wherein a plurality of unit layers are laminated along a third direction perpendicular to the first and second directions.
11. The thermally conductive sheet according to any one of claims 1 to 10, further comprising a non-anisotropic filler in the polymer matrix.
12. A method for producing a thermally conductive sheet according to any one of claims 1 to 11, A step of preparing a mixture containing a resin that is a precursor of the polymer matrix and the scaly filler; a step of subjecting the mixture to a flow orientation treatment to obtain a primary sheet while orienting the scaly filler; laminating the primary sheets to obtain a laminated block; cutting the laminated block along a lamination direction; A method for manufacturing a thermally conductive sheet comprising the steps of:
Citation Information
Patent Citations
Thermally-conductive sheet
JP2009066817A
Thermally conductive compact and manufacturing method thereof
JP2014027144A
Method of manufacturing heat-conductive sheet and heat-conductive sheet
JP2014150161A
Heat conduction sheet
JP2019112568A